Environmental conditioning: Mobile geomedia and their lines of becoming in the air, on land, and on water. (November 2022) - Thielmann, Tristan
Geomedia reflect the infrastructural, environmental, and practical conditions under which they come into being. By reading traces of and as geomedia in different natural elements, the "thick mappings" of lines presented in this article render the properties of the crossed environments visible. From a historical-anthropological perspective, geomedia have taken on a double perspective in this process since the late 18th century, with the first aerial images. With regard to the movement in the air, on land, and on water, this double mediality concerns the paradox of representing an in situ perspective and simultaneously a line of becoming. Geomedia always exhibit a documentary and a procedural form. These two characteristics are chiasmically linked with each since the Industrial Revolution. Geomedia are practices that reflexively demonstrate how the paradox can be visualized, namely, that a mediated human body on the move is in a stable position, while the surroundings are fluid.